Victorian Nights’ Entertainments: Elizabeth Gaskell and Wilkie Collins Develop the British Story Sequence - Murfin, Audrey (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractBy considering the multiple frames in and around My Lady Ludlow by Elizabeth Gaskell and “The Yellow Mask” by Wilkie Collins, this paper examines the tradition of British short stories that were structurally, but not thematically, modeled on the folktales known in England as the Arabian Nights’ Entertainments. Use of the Nights makes Victorian short fiction coherent by providing an alternative to the linear structure of the novel. This common structure is notable for the following characteristics: a deferral of knowledge and endings, repeated thematic elements across frames and stories, and embedded metafictional narratives that gesture towards oral traditions.